Sistem Informasi Pelayanan Administrasi pada Unit Layanan Terpadu ITK menggunakan Metode Waterfall - Natasia, Sri Rahayu; Septyanto, Arif Wicaksono; Wiranti, Yuyun Tri; Rohandi, Fahki (Prodi Sistem Informasi Universitas Dharma Andalas, 2024)
The ITK Integrated Service Unit (ULT) provides integrated services and information for the community related to Kalimantan Institute of Technology. The results of interviews with ITK ULTs show that the administrative service system at ITK is not fully online, especially document printing which is still done offline by ITK ULTs. This causes problems, especially the lack of responsibility of service applicants for the documents submitted. This research develops a website-based Administrative Service Information System at ULT ITK using the waterfall method, including requirements definition, system and software design, implementation, and system integration and testing. This system facilitates access to administrative services from various locations and times, and allows printing of documents after the service is completed. This research produces three main outputs: documentation of system requirements in the Software Requirements Specification (SRS), a system developed using the Laravel framework, and system test results using the black box testing method which shows the system runs well.